Relationship of Dietary Intake of Omega-3 and Omega-6 Fatty Acids with Risk of Prostate Cancer Development: A Meta-Analysis of Prospective Studies and Review of Literature - Michael E. Chua; Maria Christina D. Sio; Mishell C. Sorongon; Jun S. Dy (Prostate Cancer)
Objective. To determine the relationship between dietary omega-3 fatty acids (n-3 PUFA) and omega-6 fatty acids (n-6 PUFA) with prostate cancer risk from meta-analysis of prospective studies. Design. The literature retrieved from electronic biomedical databases up to June 2011 was critically appraised. General variance-based method was used to pool the effect estimates at 95% confidence interval. Heterogeneity was assessed by Chi2 and quantified by . Results. Eight cohort studies were included for meta-analysis. n-3 PUFA, n-6 PUFA, and their derivatives were not significantly associated with risk of prostate cancer in general. A significant negative association between high dietary intake of alpha-linolenic acid (ALA) and prostate cancer risk (pooled RR: 0.915; 95% CI: 0.849, 0.985; ) was noted. Likewise, a slightly positive association was noted on dietary long-chain n-3 PUFA, composed of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) with prostate cancer risk (pooled RR: 1.135; 95% CI: 1.008, 1.278; ); however, when two other cohort studies with data of EPA and DHA, both analyzed separately, were included into the pool, the association became not significant (RR: 1.034; 95% CI: 0.973, 1.096; ). Conclusion. Intake of n-3 PUFA and n-6 PUFA does not significantly affect risk of prostate cancer. High intake of ALA may reduce risk of prostate cancer, while intake of long-chain omega-3 fatty acids does not have a significant effect.